Logistics and Time as a Trade Barrier - Nordås, Hildegunn Kyvik (OECD Publishing, 2006)
This paper analyses the relation between time for exports and imports, logistics services and international trade. Time is found not only to reduce trade volumes, but more importantly lengthy procedures for exports and imports reduce the probability that firms will enter export markets for timesensitive products at all. Furthermore, a broader range of products are becoming time-sensitive following the proliferation of modern supply chain management in manufacturing as well as retailing. Labourintensive products such as clothing and consumer electronics are increasingly time-sensitive and many developing countries urgently need to shorten lead time in order to stay competitive in these sectors. The report argues that reforms to this effect can be implemented at relatively low cost also in low-income countries. The study provides case studies as well as econometric estimates of the relation between time, logistics services and trade performance and draws policy implications
Keywords: Trade